Recruitment using respondent driven sampling, risk behaviors assessment and willingness of young female sex workers (18–25 years) in Dar Es Salaam, Tanzania to participate in HIV vaccine trials - Mbunda, Theodora; Tarimo, Edith A. M.; Bakari, Muhammad; Sandström, Eric; Kulane, Asli (BMC public health, 2019)
Despite the present HIV preventive and treatment programs, the prevalence of HIV is still high in eastern and southern Africa, among young women and populations at high. risk for HIV transmission such as sex workers. There is a need to prepare a suitable population that will participate in efficacy HIV vaccine trials to determine the efficacy of HIV vaccines that had proven to be safe and immune potent. It was a cross-sectional study that recruited 600 female sex workers using respondent-driven sampling in Dar es Salaam. The study examined recruitment approaches, risk behaviors and willingness of young female sex workers to participate in an HIV vaccine trial. Descriptive statistics described risk behaviors and willingness of the participants to participate in efficacy HIV vaccine trials. The logistic regression model computed the likelihood of willingness to participate in the trials with selected variables. The study demonstrated 53% were less than 20 years old, 96% were single, and 22% lived in brothels. Eighty percent of the participants started selling sex at the age between 15 and 19 years old, 61% used illicit drugs for the first time when they were less than 20 years old, 24% had anal sex ever. Eighty-nine percent had more than 20-lifetime sexual partners, and 56% had unprotected sexual intercourse with sex clients. Ninety-one percent expressed a willingness to participate in the HIV vaccine trial. Sixty-one percent did not need permission from anyone for participating in a trial. Ninety-one percent expressed willingness to participate in the efficacy of HIV vaccine trial. In the logistic regression model, willingness was significantly associated with the need to ask permission for participation in HIV vaccine trial from sex agent. Respondent-driven sampling provided a rapid means of reaching young female sex workers who reported high-risk behaviors. The majority expressed a high level of willingness to participate in the HIV vaccine trial which was marginally correlated to the need to seek consent for participation in the trial from the sex brokers. Future HIV vaccine trials involving this population should consider involving the brokers in the trials because they form an essential part of the community for the participants.